EXPERIMENTAL STUDY ON EFFECT OF POLYPROPYLENE FIBER ADDITION FOR CONCRETE DUCTILITY AND DURABILITY OF CHLORIDE PENETRATION - (NIM : 25007012); Pembimbing : Dr. Ir. Saptahari Sugiri, BUDIANTO
The use of concrete in building construction there are limitations, namely the failure of structures due to brittle nature of concrete and chemical attack from the surrounding environment. One of the chemical attack on concrete in the form of chloride attack, especially the buildings in the area of the sea. One way to fix shortcomings of the brittle nature of concrete that is the addition of fiber to the concrete mix. While prevention is done to resist chloride penetration includes increasing impermeability of concrete (the use of water-cement ratio (w/c) is low), the use of high strength concrete (High Performance Concrete), the use of concrete cover is thicker than regular concrete, and add Pozolan minerals in cement mortar. This study aims to identify the compressive strength, ductility and durability of concrete to chloride penetration in normal concrete and concrete with the addition of polypropylene fibers and the substitution of cement with silica fume. Concrete strength to be achieved is 45 MPa. Tests done of concrete compressive strength, flexural ductility, and resistance testing chloride with RCPT (Rapid Chloride permeability test). In addition, it also should test the porosity and water absorption rate or sorptiviti as two issues related to transport water into the concrete. The results showed the concrete SI (0.5% Fiber +15% SF + SP), the most optimal, which has the greatest compressive strength of 51,054 MPa, the ratio I10/I5 ductility index is 2,557 (its value is smaller than the concrete SII but the difference did not too large), and resistance to chloride penetration is best (charge passed 366 (Low Chloride Ion Penetrability), depth of penetration of chloride 4.286 mm and migration coefficient 0.901 x10-12 m2/det). OPC concrete (normal) does not qualify for chloride penetration resistance, while concrete SIII (1.5% Fiber +15% SF + SP) and SIV (2% Fiber +15% SF + SP) shows the performance of ductility and resistance to chloride penetration is good but compressive strength does not qualify. Concrete SI and SII is recommended for concrete in marine environments that require high ductility and good resistance chloride.